Grundtvigs bidrag til udvikling af danske nationale symboler - Adriansen, Inge (Grundtvig-studier, 2006)
Grundtvigs bidrag til udviklingen a f danske nationale symboler[Grundtvig ’s contribution to the development of Danish national symbols]By Inge Adriansen Broadly speaking, all Danish national symbols, both official and unofficial, are to be found in Grundtvig’s authorship. However, it is difficult to specify in what way and to what degree Grundtvig inspired the dissemination of the various symbols. The most important routes of dissemination were through Den Danske Salmebog [The Danish Hymnal] and Folkehøjskolens Sangbog [The Folk-highschool Songbookl. since the corrmosition of songs weighs heaviest in Grundtvig’s literary production. This is owing to his strong belief in the significance of song in educating the people, and to his talent for bringing to life the message of song in oral form. Since both the Hymnal and the Highschool Songbook continue to be published in revised editions, they have contributed to securing Grundtvig’s significance.Grundtvig’s hymns have often been perceived as the expression of something very Danish. Therefore he was almost entirely excluded from the first hymnal produced for the Danish-speaking congregations in the Duchy of Schleswig after its incorporation into Prussia in 1867. Some of Grundtvig’s hymns were characterised by Bishop Theodor Kaftan of Schleswig-Holstein as politically dubious and having Danish national colouring.After North Slesvig’s reunification with Denmark in 1920, Grundtvig’s hymn Den signede Dag [The blessed day] gained a special status. It was sung both at the meetings in January and February before the plebiscite and at the reunification festivities over the spring and summer. When, after the summer vacation, the schools reopened under Danish leadership, Den signede Dag was everywhere sung as the first moming-hymn. The children of Slesvig were in no doubt that Grundtvig was referring to Denmark in the final verse, which begins: “ Nu rejser vi til vort Fadreland” [Now journey we to our fatherland]. In Grundtvigian homes in Slesvig the hymn was often sung at family festivities, and here it was that the tradition developed of standing up during the final verse - out of respect for the homecoming to fatherland and nation.The most significant contribution to the history of folk-education in Denmark is Grundtvig’s unitary view over hymn, historical ballad, and songs of fatherland and of folk-life. This achieves its expression in the Highschool Songbook which was first published in 1894 and has ever since helped set the norms for other Danish songbooks. The latest edition of the Highschool Songbook (from 1989) is the seventeenth, and here there are 119 songs by Grundtvig. This is 21% of the songbook’s 572 songs, and it shows that Grundtvig’s image-world continues to put its stamp upon representations of Danishness. This 17th edition was printed in over 500,000 copies, and thereby the Highschool Songbook became the Danish songbook published in the largest impression.Grundtvig has been the most significant generator of historical consciousness in Denmark, but it is a problem that only a small part of his enormous authorship and complex world of ideas is usually presented to us. At certain periods of his life Grundtvig was what many today would perceive as nationalistic. But it should be emphasised that he always stressed that Danishness has an historical and a geographical delimitation. Unfortunately there is little space within national symbolism for such complexity, and his metaphorical language was so multivalent that it has not been suited to being transposed into easily grasped symbols.Even so, this obscure metaphorical language has had a decisive significance in the development of Danish national symbolism. This is attributable in particular to the fact that Grundtvig managed to create that special interweaving of Christian, national and social identities which many Danes experience as being a matter of course and more or less of natural origin, something which has been here since the dawn of time.[Editors' note: Such terms as folkeopdragelse and folkeliv, here rendered as ‘folk-education’ and ‘folk-life’, confront Gr's translators with a special difficulty. The element folk- has little to do with the English term ‘folk-’, as in ‘folk-song’ and ‘folk-art’ with its implication of rustic or peasant provenance. Nor can it always be satisfactorily translated as ‘national’ or ‘popular’ though these can be aspects of its meaning. It essentially relates, in Grundtvigcontexts, to Gr's concept of folkelighed [‘folkliness’]: a form of social cohesion achieved by way of thinking and of conducting one's life in an enlightened and benevolent awareness of the mutual obligations and shared commitments and aspirations of a people or community identifiable by such cultural markers as a common history and a common language. In principle an inclusive concept, it nevertheless always had a potential to become exclusive in practice.]